2019
DOI: 10.14710/ik.ijms.23.4.207-214
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Mortality, and Exploitation Rate of Penaeus merguensis in the North Coast of Central Java, Indonesia

Abstract: One of the most-caught shrimp in north coast of Central Java is Penaeus merguiensis. However, little is known on the population biology of the organisms. This study was aimed to investigate length-weight relationship, growth, length at first capture (Lc50), mortality rate, and exploitation rate of P. merguiensis in Western part of Central Java’s northern coastal waters. The study was conducted from May 2016 to July 2017 using survey method. Samples were taken for 15 times (month) from 9 coastal fishing ports. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…This inverse tendency between the growth parameters CL ∞ and k observed in the present study was also registered for other peneids, e.g. F. subtilis (Santos et al, 2020), Litopenaeus schmitti (Burkenroad, 1936) (Lopes, 2012;Santos et al, 2020), Rimapenaeus constrictus (Stimpson, 1874) (Garcia et al, 2016), Penaeus merguiensis de Man, 1888 (Saputra et al, 2018), Parapenaeus fissuroides Crosnier, 1985 (Farhana & Ohtomi, 2017) and X. kroyeri (Castilho et al, 2015). The longevity estimated for both species was around 2-3 years and females showed higher values in relation to males, which was similar to observations of other authors (Villela et al, 1997;Peixoto et al, 2001;Neto, 2011;Lopes, 2012).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…This inverse tendency between the growth parameters CL ∞ and k observed in the present study was also registered for other peneids, e.g. F. subtilis (Santos et al, 2020), Litopenaeus schmitti (Burkenroad, 1936) (Lopes, 2012;Santos et al, 2020), Rimapenaeus constrictus (Stimpson, 1874) (Garcia et al, 2016), Penaeus merguiensis de Man, 1888 (Saputra et al, 2018), Parapenaeus fissuroides Crosnier, 1985 (Farhana & Ohtomi, 2017) and X. kroyeri (Castilho et al, 2015). The longevity estimated for both species was around 2-3 years and females showed higher values in relation to males, which was similar to observations of other authors (Villela et al, 1997;Peixoto et al, 2001;Neto, 2011;Lopes, 2012).…”
supporting
confidence: 86%
“…This inverse tendency between the growth parameters CL ∞ and k observed in the present study was also registered for other peneids, e.g. F. subtilis (Santos et al ., 2020), Litopenaeus schmitti (Burkenroad, 1936) (Lopes, 2012; Santos et al ., 2020), Rimapenaeus constrictus (Stimpson, 1874) (Garcia et al ., 2016), Penaeus merguiensis de Man, 1888 (Saputra et al ., 2018), Parapenaeus fissuroides Crosnier, 1985 (Farhana & Ohtomi, 2017) and X. kroyeri (Castilho et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Studies had shown that E max as the biological reference standard might lead to overly optimistic assessments, while E 10 and 0.5 standards could balance the current catches and reasonable utilisation (Gulland and Oerema, 1973;Cook, 1998). The biological reference points E 10 or 0.5 had been adopted in other species such as Penaeus indicus (Saputra et al, 2019) and Penaeus merguensis (Saputra et al, 2018). The exploitation rates of female and male swimming crabs calculated in this study were 0.61and 0.62, respectively, which were higher than the optimal rates of E 10 and 0.5, but close to the E max .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the value of L ∞ is bigger [11]. Natural mortality( M) of adult fish isn't generally controlled by fisheries operation conduct, but the position of natural mortality is important for establishing crop criteria [12].…”
Section: Discussionmentioning
confidence: 99%